2021
DOI: 10.1186/s12933-021-01385-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GLP-1 receptor agonists and SGLT-2 inhibitors on cardiac structure and function: a narrative review of clinical evidence

Abstract: The impressive results of recent clinical trials with glucagon-like peptide-1 receptor agonists (GLP-1Ra) and sodium glucose transporter 2 inhibitors (SGLT-2i) in terms of cardiovascular protection prompted a huge interest in these agents for heart failure (HF) prevention and treatment. While both classes show positive effects on composite cardiovascular endpoints (i.e. 3P MACE), their actions on the cardiac function and structure, as well as on volume regulation, and their impact on HF-related events have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 107 publications
(121 reference statements)
4
17
0
1
Order By: Relevance
“…No significant difference in hospitalization for HF was found between the two cohorts, whereas in previous in RWS SGLT-2i seem to be associated with lower risk of heart failure and total mortality comparing new users of SGLT-2i and GLP-1RA [ 17 19 ]. SGLT-2i displayed an unparalleled benefit on HF-related outcomes in randomized controlled trials regardless of the baseline cardio-renal risk of the enrolled population [ 29 ]; accordingly, a meta-analysis of RWS showed that SGLT-2i were more effective than GLP-1RA on prevention of HF worsening [ 30 ]. On the other hand, albeit to a lesser extent, GLP-1RA have also been proven beneficial, significantly reducing HF hospitalization by 11% compared to placebo in CVOT [ 2 ] and by 12% compared to other glucose-lowering drugs except for SGLT-2i in RWS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant difference in hospitalization for HF was found between the two cohorts, whereas in previous in RWS SGLT-2i seem to be associated with lower risk of heart failure and total mortality comparing new users of SGLT-2i and GLP-1RA [ 17 19 ]. SGLT-2i displayed an unparalleled benefit on HF-related outcomes in randomized controlled trials regardless of the baseline cardio-renal risk of the enrolled population [ 29 ]; accordingly, a meta-analysis of RWS showed that SGLT-2i were more effective than GLP-1RA on prevention of HF worsening [ 30 ]. On the other hand, albeit to a lesser extent, GLP-1RA have also been proven beneficial, significantly reducing HF hospitalization by 11% compared to placebo in CVOT [ 2 ] and by 12% compared to other glucose-lowering drugs except for SGLT-2i in RWS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in three nested case–control studies involving 336,334 T2D patients without previous CV disease and HF, Wright et al have recently shown that GLP-1RA were associated with a 18% risk reduction of HF compared to other glucose-lowering drugs [ 25 ]. However, Natali et al recently reviewed the available clinical studies on GLP-1R agonism and left ventricular function, concluding that its role is still unclear in patients with both preserved or reduced left ventricle ejection fraction [ 30 ], despite the encouraging results of preclinical studies [ 31 ]. Further evidence is warranted to better understand the potential benefit of GLP-1RA in patients with HF; relevant to this question, the STEP-HFpEF trial is currently assessing the effect of semaglutide 2.4 mg once weekly in patients affected by HF with preserved ejection fraction (NCT04788511).…”
Section: Discussionmentioning
confidence: 99%
“…No significant change in structural parameters were appreciated at resting 2D echocardiography; similarly, despite a trend towards improved values, diastolic function was also unchanged in the two intervention groups, both at rest and during exercise. SGLT2i have been inconsistently associated with an amelioration of LV structural and functional parameters in T2D subjects without overt HF and/or structural heart disease[ 2 ]. Sitagliptin has been shown to improve E/e′ by 20% in a population similar to ours, but only after 24 months [ 18 ], and empagliflozin has been reported to ameliorate diastolic function in subject with HFrEF and moderate to severe diastolic dysfunction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with type 2 diabetes mellitus (T2D) and at high cardiovascular risk, hospitalization for heart failure (HF) were reduced by 30–40% already after 6 months of treatment with empagliflozin independently from the presence of established HF at baseline [ 1 ]. Nonetheless, the mechanisms of the cardioprotective properties that are present irrespective of the presence of T2D, the amelioration in glycaemic control, blood pressure, and body weight, remain ill-defined [ 2 ], particularly in subjects devoid of heart and kidney disease, wherein the effect on body fluid volume regulation—considered a pillar of SGLT2i mechanism of action [ 3 ]—is unlikely to play a relevant role. Alternative pharmacological actions have been suggested, namely: improved muscle oxygen/work coupling driven by a larger availability of oxygen (through increased plasma haemoglobin), the use of more efficient metabolic substrates (ketone bodies [ 4 ]), and/or a direct effect on myocardial contractility through the inhibition of the Na/H exchanger [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason is the heterogeneity in the CVD risk of the study populations. Besides, SGLT2 inhibitors may primarily target on ameliorating cardiac structure and function (“the pump”) and not on the “pipes” (coronary arteries) [ 113 , 114 ]. Patients with T2DM and cardiac hypertrophy, diastolic or systolic dysfunction or with a hypervolemic state (regardless of cardiac or renal origin) are the best candidates for treatment with SGLT2 inhibitors [ 114 ].…”
Section: Clinical Evidence Of Sglt2 Inhibitors Against Cvdmentioning
confidence: 99%